2006
DOI: 10.1576/toag.8.3.153.27250
|View full text |Cite
|
Sign up to set email alerts
|

Symphysis pubis dysfunction: a practical approach to management

Abstract: Symphysis pubis dysfunction is a relatively common and debilitating condition affecting pregnant women. It is painful and can have a significant impact on quality of life, which can lead to potentially serious complications such as depression. Effective management remains difficult to determine because of a variation in reported occurrence rates and symptomatology. There is little published assessment of treatments and no standardised management protocols are available. This article describes recent developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 22 publications
0
34
0
12
Order By: Relevance
“…In cases of continuing pregnancy, therapy is similar. Jain et al showed that an indication for C-section with symphyseal widening causing a change to the birth canal, or when hip abduction is severely restricted [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of continuing pregnancy, therapy is similar. Jain et al showed that an indication for C-section with symphyseal widening causing a change to the birth canal, or when hip abduction is severely restricted [17].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic, enzymatic, traumatic and also degenerative factors have been reported as causes of symphysis widening (see Table 1) [15,16]. Overall, faulty endocrine regulation and concomitant laxity of the symphyseal ligamentous apparatus appear responsible for symphyseal rupture; however, the exact pathogenesis cannot be detected [17].…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…7% des parturientes ont cette symptomatologie en post partum [3, 4]. Les étiologies de cette affection restent mal connues bien que plusieurs auteurs ont rapporté l'association fréquence de la disjonction symphysaire et certains facteurs de risque notamment la macrosomie foetale, les manoeuvres d'extraction, les pathologies articulaires et les traumatismes de l'articulation pubienne [5, 6].…”
Section: Discussionunclassified
“…The increase in pubic symphysis spacing is normally small, usually on the order of 2-5 mm (Becker et al, 2010;Herren et al, 2015) and normally no more than 10 mm (Senechal, 1994;Shanghai First Medical College, 1978). In rare cases, diastasis (abnormal separation of the symphysis) may occur secondary to factors such as large foetal size; this is characterized by separation of 10 mm or more and can be associated with significant postpartum pain and difficulty walking (Herren et al, 2015;Jain, Eedarapalli, Jamjute, & Sawdy, 2006). In the case of M70-1, field observations showed an in situ pubic symphysis opening of about 3.5 cm.…”
Section: Interpreting Events During Birthmentioning
confidence: 99%